Measuring health-related quality of life in cardiovascular disease using a novel patient-centred and disease-specific patient-reported outcome measure - Tajinder K. Singh; Daan Ties; Hilde E. Groot; Paul F.M. Krabbe; Pim van der Harst (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Background: Assessment of health-related quality of life (HRQoL) in patients with cardiovascular disease (CVD) is impaired by limitations of current patient-reported outcome measures (PROMs). We developed the first cardiovascular disease (CVD) specific electronic PROM for which health items were derived by a fully patient-centered method. This paper reports on the measurement of HRQoL in CVD patients by a novel developed electronic patient-centred PROM based on a preference-based measurement model. Methods and results: In an earlier patient-based study nine health items were selected as most important to CVD patients. These items were assessed in the novel preference-based PROM of this study. CVD patients registered with a Dutch patient organization were asked to rate their health state. We compared HRQoL between subgroups of age, gender and CVD. A total of 554 patients participated in this study. The patient reported health items “worry”, “self-reliance” and “sexuality” had the highest impact on HRQoL of CVD patients. Median HRQoL was better for men compared to woman (−17.04, IQR: 31.47 to −3.91 vs. −25.22; IQR: 42.06 to −9.53, p = 0.003). Best and worst HRQoL were observed in patients with an unknown or other CVD disease (−15.61, IQR: 28.52 to −3.91) followed by individuals with coronary artery disease (−16.99, IQR: 38.08 - 0.00) and heart failure (−24.27, IQR: 42.64 to −12.98). Conclusions: This novel patient-centred, preference-based, CVD-specific PROM accurately measures HRQoL by taking individual health preferences into account and tackling limitations of current PROMs. This PROM is therefore promising to evaluate interventions and optimize personalized therapies.